2010
DOI: 10.1038/ki.2010.23
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of SBR759, a new iron-based phosphate binder

Abstract: Treatment of elevated serum phosphorus in hemodialysis patients remains challenging due in part to the lack of a well-tolerated, safe, and effective phosphate binder. Here we report the results of a single-center, open-label, phase I clinical trial of 44 hemodialysis patients to show the safety and efficacy of a novel iron-based phosphate binder, SBR759. After establishing its safety at an initial dose of 3.75 g/day, SBR759 was given to successive cohorts in several divided doses of up to 22.5 g/day. The defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…Several studies have shown that ferric compounds, including SBR759 and PA21, have serum phosphorus-reducing effects in hemodialysis and predialysis CKD patients; however, a relatively high dose of these compounds may be required to obtain efficacy [13,14,15,16,17,18]. Ferric citrate hydrate (JTT-751) is a novel calcium-free phosphate binder, currently being developed as a treatment for hyperphosphatemia in CKD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that ferric compounds, including SBR759 and PA21, have serum phosphorus-reducing effects in hemodialysis and predialysis CKD patients; however, a relatively high dose of these compounds may be required to obtain efficacy [13,14,15,16,17,18]. Ferric citrate hydrate (JTT-751) is a novel calcium-free phosphate binder, currently being developed as a treatment for hyperphosphatemia in CKD patients.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 JTT-751 has a larger surface area and faster dissolution rate than ferric citrate, and is expected to demonstrate efficacy as a phosphate binder. 12 SBR759, an iron (III) oxide-hydroxide (FeO(OH))-starch-sucrose-carbonate complex, 13 binds to phosphates in food via ligand exchange mechanism in the gastrointestinal tract. Sucroferric oxyhydroxide (PA21) is a new calcium-free polynuclear iron(III)-oxyhydroxide phosphate binder with a high phosphate binding capacity over a wide pH range.…”
Section: Introductionmentioning
confidence: 99%
“…SBR759, a polymeric complex composed of iron (III) oxide and starch, and PA21, a stabilized polynuclear iron (III) oxyhydroxide, have serum P-reducing effects in hemodialysis and predialysis CKD patients; however, a relatively high dose of these compounds may be required to obtain efficacy [18,19,20]. …”
Section: Introductionmentioning
confidence: 99%